Study on antihyperglycemic effect of bromocriptine in dexamethasone induced hyperglycemic wistar rats - M. B., Rekha; Bhandare, Basavaraj; V., Satyanarayana; M. B., Hemamalini (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Diabetes mellitus is a chronic metabolic disorder that develops due to insulin deficiency or insulin resistance. Recent animal and human studies have reported bromocriptine to be effective in the management of type 2 diabetes mellitus. The present study was done to evaluate the antihyperglycemic effect of bromocriptine in dexamethasone induced hyperglycemic rats. Methods: Male wistar rats were used and divided into 5 groups. Dexamethosone was used to induce hyperglycemia in group B-E. Group A was the untreated control group, group B was the standard control group, group C was the oral 10 mg/kg of bromocriptine dissolved in 0.9% normal saline, group D was the oral 20 mg/kg metformin dissolved in 0.9% normal saline, group E was the oral 10 mg/kg bromocriptine+20 mg/kg metformin dissolved in 0.9% normal saline. Fasting blood glucose, post prandial blood glucose and body weight was estimated on day 1, 15, 30. Results: It was seen that dexamethasone induced hyperglycemia and increase in body weight in male wistar rats, which were significantly controlled by oral bromocriptine and bromocriptine with metformin combination. Conclusions: Results obtained from this study showed that bromocriptine can be a promising drug with novel mechanism to treat type 2 diabetes mellitus.